Unveiling whole body vibration squat intensity insight from oxygen consumption and heart rate response - Zhengji Qiao; Feifei Li; Zhengyang Ye; Longyan Yi; Yanchun Li; Bing Yan; Yang Wang (Scientific Reports)
Abstract This study explored the effects of training weight and amplitude in whole-body vibration (WBV) on exercise intensity, indicated by oxygen consumption (VO2) and heart rate. In LOAD-study: ten participants performed squats under non-WBV and WBV (30 Hz 2 mm) conditions at 0%, 40%, and 80% bodyweight (BW). In AMPLITUDE-study: eight participants performed squats under non-WBV, low-amplitude WBV (30 Hz 2 mm), and high-amplitude WBV (30 Hz 4 mm) conditions with 0% and 40%BW. heart rate and VO2 were continuously recorded. Metabolic equivalents (METs) for WBV squats with 0–40% BW were ~ 3.8–5.3, and ~ 7.3 for 80% BW. LOAD-study presented a significant vibration × training weight interaction effect for in-exercise VO2 (F = 3.171, P = 0.05, η p 2  = 0.105) and post-exercise VO2 (F = 4.156, P = 0.021, η p 2  = 0.133). In-exercise VO2 of 80%BW squat (P < 0.001) and post-exercise VO2 of both 40% (P = 0.049) and 80%BW squat (P < 0.001) under WBV were significantly higher than those under non-WBV. AMPLITUDE-study presented no significant amplitude × training weight interaction effect for VO2 and heart rate (P > 0.05). WBV squats are moderate-to-vigorous intensity exercise. 30 Hz 2 mm WBV is sufficient for evoking superior oxygen consumption during and after exercise under certain training weight, the response of heart rate to WBV was less pronounced. Increasing training weight could elicit greater oxygen consumption and heart rate under WBV condition.